ZONASI DAN KOMPOSISI VEGETASI HUTAN MANGROVE PANTAI CENGKRONG DESA KARANGGANDU KABUPATEN TRENGGALEK PROVINSI JAWA TIMUR - Ahmad Mughofar; Mohammad Masykuri; Prabang Setyono (Graduate School Bogor Agricultural University (SPs IPB), 2018)
A research on mangrove forest at coast Cengkrong in the village of Karanggandu aimed at defining zoning and composition of magrove vegetation. The sampling method consists of 3 zoning. Each zone established 3 plots, consists of 10 m x10 m plot size of trees category, 5 m x 5 m of stake category, and 1 m x 1 m of seedling category to repeat in 3 times. Data analysis of mangrove vegetation employed Improtance Value Indeks (IVI). The research results found 12 mangrove species namely Avicennia alba, Bruguiera gymnorrhiza, Bruguiera parviflora, Ceriops decandra, Ceriops tagal, Lumnitczera racemosa, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, Sonneratia caseolaris, Xylocarpus granatum Nypa fruticans. Reffering to the the mangrove zonation indicates the zone I or open zone grows Sonneratia alba and it can be found Rhizophora mucronata, Ceriops decandra with salinity of 6 ppt. Zone II or middle zone grows species of Avicennia alba and it also be found Sonneratia alba, Xylocarpus granatum with salinity of 6 ppt. Zone III or zone that is closer to the landward grows species Xylocarpus granatum and also appears Lumnitzera racemosa,Bruguiera parviflora with salinity of 4 ppt. It showed that the formation of mangrove zonation at Coast Cengkrong is still categorized as less stable, due to rehabilitation since 2002 were done without understanding the type of site suitability and natural factors which causes the fruits drop when the tides of sea water, so that the growth is not stable.